Higher arterial stiffness and systolic blood pressure are differentially associated with lower perfusion in subcortical and cortical gray matter regions. (20th December 2022) - Lipford, Megan E.; Lockhart, Samuel N.; Coffin, Claudia Ashlyn; Suerken, Cynthia; Bateman, James R.; Barcus, Richard A.; Whitlow, Christopher T.; Craft, Suzanne; Hughes, Tim M.
Abstract: Background: Higher arterial stiffness is associated with lower regional cerebral blood flow (CBF) in older adults. Cortical CBF also correlates with higher systolic blood pressure (SBP). We examined relationships of lobar and deep gray matter CBF with both SBP and arterial stiffness. Method: Participants of the Clinical Core of the Wake Forest Alzheimer's Disease Research Center completed baseline clinical examination including measures of: arterial stiffness, blood pressure, medication review, APOE genotyping, 3T MRI, detailed cognitive testing, and cognitive adjudication. T1 structural and pseudocontinuous arterial spin labeling (pcASL) MRI were used to quantify gray matter (GM) CBF in AAL atlas regions. GM CBF was quantified into lobar (frontal, temporal, parietal, occipital), subcortical (caudate, putamen, pallidum, and thalamus), Cingulate/Insula, and posterior (cerebellum and vermis) regions. Arterial stiffness was measured twice in the supine position and averaged to quantify carotid‐femoral pulse wave velocity (cfPWV). Associations for cfPWV and systolic blood pressure (SBP) with GM CBF ROIs was examined by multivariable linear regression models adjusted for age, race, gender, education, hypertension medications, and APOE ‐e4 carrier status. Result: Among 404 participants (70±8 years; 39 dementia, 139 MCI, 226 normal cognition), higher cfPWV and SBP were differentially associated with regional GM CBF (Fig 1 & 2). Higher cfPWV was associated with lower subcortical GM CBF (p=0.04) (Table 1). Higher SBP was associated with lower GM CBF in frontal (p=0.03), temporal (p=0.02) and occipital lobes (p=0.01) (Table 1). Conclusion: Deep subcortical brain structures may be at greater risk of damage from high arterial stiffness because they are perfused by arteries which branch relatively upstream of other branching arteries, as evidenced by lower GM CBF. High SBP may predict vascular damage in cortical regions manifested as lower GM CBF. These differential relationships with deep and cortical perfusion support and extend prior observations in this group relating vascular risk factors to abnormalities in white matter micro‐ and macro‐ structure, lower total CBF, and lower cognitive performance.